ANTI-BULLYING EDUCATION FOR THE MOSLEM MILLENNIAL GENERATION IN UIN MAULANA MALIK IBRAHIM MALANG - Muhajir, As'aril; Budi Harianto; Bobby Rachman Santoso; Pianto, Heru Arif (University of Islam Malang, 2025)
Anti-bullying education is a strategic initiative to prevent and address intimidation in educational environments, particularly among the Moslem millennial generation who are vulnerable to the interplay of social dynamics and rapid technological developments. While previous studies have examined bullying from various perspectives—such as Islamic educational principles, self-control development, and cognitive-behavioral interventions—there is limited research integrating Islamic education values with Stoicism philosophy in the context of higher education. This study addresses that gap by exploring the implementation of anti-bullying education at the State Islamic University (UIN) Maulana Malik Ibrahim Malang and assessing the effectiveness of its integrated approach. Employing a descriptive qualitative method, data were collected through interviews with students, lecturers, and educational staff involved in anti-bullying programs. The findings reveal that combining Islamic ethical principles with Stoic concepts of self-discipline and resilience can foster a more inclusive and bullying-free campus culture. The study also highlights the role of technology and social media in both perpetuating and preventing bullying. Recommendations are provided for strengthening the character education curriculum, integrating moral philosophy into student development programs, and enhancing institutional policies to create a safer and more supportive academic environment.